Soyamilk fermented with riboflavin-producing Lactobacillus plantarum CRL 2130 reverts and prevents ariboflavinosis in murine models - Juarez del Valle, Marianela (2016)
It has been previously shown that Lactobacillus plantarum CRL 2130 is able to produce riboflavin in soyamilk. The aim of the present study was to evaluate the efficiency of this riboflavin-bio-enriched soyamilk to revert and/or prevent the nutritional deficiency of riboflavin using different animal models. When used to supplement the diets of previously depleted animals, it was shown that the growth, riboflavin status and morphology of the small intestines reverted to normal parameters and were similar to animals supplemented with commercial riboflavin. In the prevention model, the same tendency was observed, where animals that received soyamilk fermented with L. plantarum CRL 2130 did not show signs of riboflavin deficiency. This new bio-fortified soya-based product could be used as part of normal diets to provide a more natural alternative to mandatory fortification with riboflavin for the prevention of its deficiency.